Pengembangan Indeks Prediksi Risiko Hipertensi Berdasarkan Indeks Massa Tubuh (IMT) dan Rasio Lingkar Pinggang-Pinggul (RLPP) pada Pasien Dewasa di Puskesmas Wonokasian Kabupaten Sidoarjo - Hamid, Zainudin; Anggraini, Novita Ana; Wahjuni, Chatarina Umbul (Lembaga Teewan Journal Solutions, 2026)
Hypertension is a global health problem and a leading cause of cardiovascular morbidity and premature death. Its risk is influenced by various factors, including age, general obesity, and central obesity. Body Mass Index (BMI) reflects general obesity, while the Waist-to-Hip Ratio (WHR) indicates body fat distribution or central obesity. However, simple, practical, and applicable models for predicting hypertension risk in primary health care remain limited. This study aims to analyze the effects of age, BMI, and WHR on hypertension incidence and to develop a prediction model for hypertension risk among adult patients at the Wonokasian Community Health Center in Sidoarjo Regency. This analytical observational study employed a cross-sectional design involving 411 adult patients. Data collected included respondent characteristics and anthropometric measurements such as body weight, height, BMI, waist circumference, hip circumference, WHR, and blood pressure. Data analysis was performed using bivariate tests and binary logistic regression. Model performance was evaluated using the Hosmer-Lemeshow test, the Area Under the Receiver Operating Characteristic Curve (AUC-ROC), sensitivity, and specificity. The results indicate that age, BMI, and WHR significantly influence the incidence of hypertension in adult patients. The prediction model based on these variables performs quite well and has the potential to serve as a simple, practical, non-invasive, and applicable tool for initial hypertension risk screening in primary health care.